2018
DOI: 10.29079/vol17iss1art478
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and histological study of the thymus gland in native rabbits (Oryctolagus cuniculus)

Abstract: The aim of this study is to add the available information of the anatomy and documenting the normal microscopic features of the thymus gland in rabbits, for this reason ten rabbits from the local breed aged between (5-7) weeks breeding in animal house. After anesthetic the healthy animals intramuscularly in the thigh, the thoracic cavity opening by surgical scissor, to entering the thymus to study it anatomically and collected the specimen for histological study. The animals divided into two groups: first grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The outermost layer of the stomach is the tunica serosa consisting of blood vessels, nerves, and areolar adipose connective tissue, this tunica was stretched and in certain places, it blends in with the former tunic. The last three layers have the same histological structure along of stomach wall and similar to those reported by (Khalel and Ghafi, 2012;de Sousa Cavalcante et al, 2021). The fundic region was the largest and took up the whole space in the stomach between the pyloric and cardiac regions.…”
Section: Stomachsupporting
confidence: 85%
See 1 more Smart Citation
“…The outermost layer of the stomach is the tunica serosa consisting of blood vessels, nerves, and areolar adipose connective tissue, this tunica was stretched and in certain places, it blends in with the former tunic. The last three layers have the same histological structure along of stomach wall and similar to those reported by (Khalel and Ghafi, 2012;de Sousa Cavalcante et al, 2021). The fundic region was the largest and took up the whole space in the stomach between the pyloric and cardiac regions.…”
Section: Stomachsupporting
confidence: 85%
“…The wall of each region had four basic layers: mucosa, submucosa, muscularis, and serosa (figs 3_9, 10). As mentioned in the study of (Khalel and Ghafi, 2012) for rabbits, the cardiac area revealed a tiny, folded region encircling the esophageal opening. The simple columnar epithelium lines the cardiac region's tunica mucosa.…”
Section: Stomachmentioning
confidence: 62%
“…In each lobule there is a cortex and a medulla. The body is based on epithelial D. E. Rahmoun, M. A. Lieshchova, S. Chaanbi, S. Chergui Study of anatomical, histological and cytological characteristics of the thymus of lambs tissue, made up of epithelial cells, research has been done on the rabbit by the authors (Khaleel et al, 2018), who found the same results.…”
Section: Discussionmentioning
confidence: 95%